The Correlation of Nutritional Status and Acute Respiratory Tract Infections for Children Under Five in West Halmahera - Mamahit, Adi Yeremia; Legi, Julita; Karame, Verra; Pondete, Marlyn Anggelina; Tubol, Inggita Natalia (Jurnal Ners, 2024)
Acute respiratory tract infections (ARIs) are still a public health problem at present. This disease is very dangerous because it can be a precursor to pneumonia and stunting in children. The aim of this research is to determine the relationship between nutritional status and the incidence of ARIs in Akelamo Village, East Sahu District, West Halmahera Regency, North Maluku Province, Indonesia. Crosssectional methods were used in this research. The total population was 52 children which were then calculated using proportional sampling techniques to obtain 37 children as the research sample. The research results show that the child's nutritional status and the mother's education level have a significant relationship with the occurrence of ARIs. Therefore, the role of health workers is very necessary to provide education about the use of local food to improve children's nutrition and education about preventing ARIs needs to be carried out more intensively.